Implementasi Media Pembelajaran Berbasis Proyek pada Materi Sistem Gerak: Uji Coba Skala Kecil - Ula, Attaqotul; Harun, Naura Maheshi; Mahdiannur, Muhamad Arif; Subekti, Hasan (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2022)
The process of implementing the selection of instructional media is essentially one application of learning technology. This research is the implementation of project-based learning in which learners will create teaching aids to study the basic competencies of the motion system. This research belongs to research design with a small-scale class trial. This research involves five randomly selected learners. Questionnaire instruments were used to measure the interest and motivation of learners after the small-scale class trial. The results of the small-scale class trial show that student interest is predominantly low, with a percentage of 25% regarding teaching aids-based instructional media, while the results of the small-scale class trial indicate that learner motivation agrees, with a percentage of 47% regarding student motivation instruments in instructional media. Learner responses to teaching aids and instructional media are quite positive, with a percentage of 60%, and they provide feedback related to providing more visuals and more appealing fonts. The implementation of project-based learning with teaching aids media in the small-scale class trial shows a positive trend and serves as a basis for improving teaching aids media for use in larger-scale class trials. Keywords: teaching aid, learning media, skeletal and muscular system